Generalized Jensen and Jensen–Mercer inequalities for strongly convex functions with applications - Ivelić Bradanović, Slavica; Lovričević, Neda (Journal of inequalities and applications, 2024)
Strongly convex functions as a subclass of convex functions, still equipped with stronger properties, are employed through several generalizations and improvements of the Jensen inequality and the Jensen–Mercer inequality. This paper additionally provides applications of obtained main results in the form of new estimates for so-called strong f -divergences: the concept of the Csiszár f -divergence for strongly convex functions f , together with particular cases (Kullback–Leibler divergence, χ 2 -divergence, Hellinger divergence, Bhattacharya distance, Jeffreys distance, and Jensen–Shannon divergence.) Furthermore, new estimates for the Shannon entropy are obtained, and new Chebyshev-type inequalities are derived.